Determination of optimal work start time - Li, Shu-Guang (Transport, 2007)
The question is: whether the system total travel cost and travel time are reduced by adjusting the work start time or not? This paper proposes the two‐level model for answering the question; the upper‐level minimizes the system travel cost and travel time by using the work start time as a decision variable, the lower‐level models the stochastic dynamic simultaneous route/departure time equilibrium problem. Finally, numerical results of a small network are provided to illustrate the behavior of the model. First Published Online: 27 Oct 2010